EVALUASI PENGEMBANGAN UMKM KABUPATEN ROKAN HULU MENGGUNAKAN BUSINES MODEL CANVAS - Purwantoro, Purwantoro (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2019)
Micro Small medium enterprises (UMKM) in each state specifically in the ASEAN region faced with the situation of global competition. A very tight competition is forcing businessmen to become the best. One of the ways that it can be reached by the trade to be able to be the best business strategy is appropriate, effective and efficient. This research aims to find out how the application business model canvas in creating alternative business strategies for the development of UMKM. The second objective is to know the proper strategic alternatives for the development of UMKM. The methods used in this research is descriptive qualitative approach with the use of informants as respondents research. The data source used is the business owners as much as 16 UMKM who open businesses in the downtown area of Pasir Pengaraian. Data collection techniques using interview techniques directly, observation and documentation. This research uses a template business model canvas to map strategy for the effort and combined with the SWOT analysis. Based on data obtained from the results of research, that the description of the business model approach UMKM using Business Model Canvas outline can be used as recommendations for business strategy, the business model which is currently already underway is able to meet the Nine elements of the blocks on the template business model canvas. The findings of this research are that not all the UMKM business strategy and have just run a business without the vision of enterprise development. Based on the results of the SWOT analysis can be found that alternative new efforts by optimizing internal strength in revenue streams on each UMKM and conduct elections to the right customer segments. Suggestions that may the researcher pointed out every UMKM should be more daring to have the vision to grow and continue to innovate against products goods or services, increase customer segmentation and make use of business model canvas approach in making the strategy of the business.